Incidence and long‐term outcomes of surgically treated childhood hepatic malignancies in Finland. (25th August 2019) - Tiusanen, Toivo; Hukkinen, Maria; Leskinen, Outi; Soini, Tea; Kanerva, Jukka A.; Jahnukainen, Timo; Mäkisalo, Heikki; Heikinheimo, Markku; Pakarinen, Mikko P.
Abstract: Aim: To analyse incidence, treatment and outcomes of paediatric liver malignancies in Finland during 1987‐2017. Methods: Medical records and national cancer registry data of 47 children with liver malignancies were reviewed. Survival was calculated with the Kaplan‐Meier method. Results: During follow‐up, liver malignancy incidence remained stable at 1.1:10 6 . Altogether, 42 patients with hepatoblastoma (n = 24), hepatocellular carcinoma (n = 11) and undifferentiated embryonal sarcoma (n = 7) underwent surgery at median age 4.6 (interquartile range, 2.0‐9.6) years and were followed up for 13 (7.0‐19) years. Cumulative 5‐year survival was 86% for hepatoblastoma, 41% for hepatocellular carcinoma and 67% for undifferentiated embryonal sarcoma. Five‐year survival was decreased among hepatoblastoma patients aged ≥ 2.4 years (73% versus 100%, P  = .040), with PRETreatment EXTent of disease IV (PRETEXT, 60% vs 100%, P  = .004), and with recurrent disease (67% vs 88%, P  = .029). Recurrent/residual disease associated with decreased 5‐year survival in hepatocellular carcinoma (0% vs 83%, P  = .028). Survival was similar among 19 transplanted and 23 resected patients. In total, 14 deaths occurred either for the underlying malignancy (n = 8), adverse effects of chemotherapy (n = 5) or unrelated reasons (n = 1). Conclusion: Outcomes for PRETEXT I‐III hepatoblastoma and un‐metastasized hepatocellular carcinoma were encouraging. Adverse effects of chemotherapy significantly contributed to mortality.